ANALISIS KESULITAN BELAJAR PESERTA DIDIK MEMBACA AL-QUR’AN PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS X BIM ISLAMIC SCHOOL - Budi Prasetyo, Wisnu; Farhan, Muhammad; Rahayu Aulia, Fatihani (LP2M JAMIAT KHEIR, 2025)
This study aims to describe the form of difficulties in learning to read the Quran experienced by students in the subject of Islamic Religious Education in class X BIM ISLAMIC SCHOOL This research is classified as field research with a type of qualitative research. The data sources in this study are school principals, Islamic Religious Education teachers and students as primary data sources and documents as secondary data sources. The data in this study was collected by conducting observations, interviews, and documentation. The data was processed and analyzed through three stages, namely data reduction, data presentation, and conclusion drawn. The results of the study showed that the forms of difficulties in reading the Qur'an for students varied, some had difficulty in pronouncing the letters according to the makhraj, and some had difficulty reading when connecting letters with other hijaiyah letters. And it is difficult to read the Qur'an according to tajweed.